1986
DOI: 10.1104/pp.82.1.203
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Isozyme System of 3-Deoxy-d-arabino-Heptulosonate 7-Phosphate Synthase in Nicotiana silvestris and Other Higher Plants

Abstract: Two isozymes of 3-deoxy-D-arabino-heptulosonate 7-phosphate (DAHP) synthase, denoted DS-Mn and DS-Co, were identified following DEAE-cellulose chromatography of crude extracts prepared from suspension-cultured cells of Nicotiana silvestris. The strikingly different properties of the isozymes allowed the development of assays for the selective detection of either isozyme in samples containing a mixture of the two. The DS-Mn isozyme required the sulfhydryl reductant, dithiothreitol, for activity and was stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…Other enzymes in the aromatic amino acid pathways, such as 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase, 5-enolpyruvylshikimate-3-phosphate synthase, and tryptophan synthase A, have similar leader sequences and were shown biochemically to be present in chloroplasts (11,14,21,25).…”
Section: Discussionmentioning
confidence: 99%
“…Other enzymes in the aromatic amino acid pathways, such as 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase, 5-enolpyruvylshikimate-3-phosphate synthase, and tryptophan synthase A, have similar leader sequences and were shown biochemically to be present in chloroplasts (11,14,21,25).…”
Section: Discussionmentioning
confidence: 99%
“…CM-2 has been proposed to be part of a complete cytosolic shikimate pathway that, in addition to supplying aromatic amino acids for protein synthesis, also provides precursors for secondary metabolism (8). This suggested that an increase in secondary metabolism might be correlated with an increase in CM-2 activity, particularly since isozymic forms of DAHP synthase demonstrated differential timing of their expression in Nicotiana silvestris suspension cultures (2,3). In these cultures, the plastid associated DAHP synthase demonstrated maximum activity during early exponential growth, whereas the cytosolic isozyme activity was greatest during late exponential growth.…”
Section: Resultsmentioning
confidence: 99%
“…The hysteric nate 7-phosphate (DAHP) synthase (EC 4.1.2.15) modulation of DS-Mn in the presence of dithio-(DS) which difTered dramatically in physical, cata-threitol was interpreted by Ganson et al (1986) to lytic and regulatory properties were first described in imply its redox regulation by thioredoxin. higher plants by Rubin & Jensen (1985), using Vigna…”
Section: Introduction ^ Similar Subcellular Compartmentation Have Beenmentioning
confidence: 99%
“…A survey of crude extracts from a variety of plant sources indicated that the DS-Co/DS-Mn isoenzyme pair may be universally present in higher plants (Ganson et al, 1986).…”
Section: Introduction ^ Similar Subcellular Compartmentation Have Beenmentioning
confidence: 99%